2009
DOI: 10.1310/tsr1603-212
|View full text |Cite
|
Sign up to set email alerts
|

Driving Status and Community Integration After Stroke

Abstract: Driving status has unique and substantial influence on community integration following stroke. Social support facilitated community integration but did not substantially buffer the effects of driving cessation. Although men and women resumed driving at equal rates, driving cessation showed differential effects for men and women in regard to their community integration. Research is needed to design interventions that promote full engagement in community living among persons who cease driving after stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 45 publications
1
31
0
2
Order By: Relevance
“…There was one article that was specific to individuals with stroke (Griffen et al, 2009) and a study reported over two articles that was unique to individuals with TBI (Liddle et al, 2011;Liddle, Fleming, et al, 2012). In all the articles, there was an almost equal distribution of spouses and other family members (Griffen et al, 2009;Liddle et al, 2011;Liddle, Fleming, et al, 2012 Prior to stopping driving, 63% of females were taking household shopping trips compared to 34% of the males.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There was one article that was specific to individuals with stroke (Griffen et al, 2009) and a study reported over two articles that was unique to individuals with TBI (Liddle et al, 2011;Liddle, Fleming, et al, 2012). In all the articles, there was an almost equal distribution of spouses and other family members (Griffen et al, 2009;Liddle et al, 2011;Liddle, Fleming, et al, 2012 Prior to stopping driving, 63% of females were taking household shopping trips compared to 34% of the males.…”
Section: Resultsmentioning
confidence: 99%
“…There was one article that was specific to individuals with stroke (Griffen et al, 2009) and a study reported over two articles that was unique to individuals with TBI (Liddle et al, 2011;Liddle, Fleming, et al, 2012). In all the articles, there was an almost equal distribution of spouses and other family members (Griffen et al, 2009;Liddle et al, 2011;Liddle, Fleming, et al, 2012 Prior to stopping driving, 63% of females were taking household shopping trips compared to 34% of the males.  Individuals who were driven by family members for non-essential travel (e.g., leisure trips) rose from 17 to 76%  13% of caregivers reported giving up the worker role while 33% reported missing work occasionally  58% of family members rated the older driver's driving as "good" or "excellent" while 81% individuals did so (p=0.0342)  Regarding driving decisions, 42% of family members and 11% of older drivers felt that they should not be driving (p=0.0027)  While the older driver reported that advice to stop driving all came from their adult children, family members reported that the older driver's friends (22%), adult children (67%) and spouses (11%) had advised as well.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations